Licenciaturas em matemática de instituições públicas de educação superior no estado de Mato Grosso : um estudo sobre os conhecimentos de como ensinar presentes nos projetos pedagógicos de cursos - Silva, Raquel de Lima (2020)
The present research entitled “Mathematics Degree in Public Institutions of Higher Education in the State of Mato Grosso: a study on the knowledge of how to teach present in the Pedagogical Projects of Courses” developed in the Postgraduate Program in Education, in the line of Education Science and Mathematical Education at the Federal University of Mato Grosso (UFMT), together with the Group of Studies and Research in Mathematical Education (GRUEPEM). We seek in this work to investigate what the Pedagogical Projects of Courses (PPC) of Degree in Mathematics presential what they denote in state of Mato Grosso of how the initial training of teachers has been proposed regarding the knowledge of how to teach. The guiding question of the research was the following: What knowledge of how to teach is present in the Pedagogical Course Projects (PPC) of Public Institutions of Higher Education in Mathematics Licenciaturas in the state of Mato Grosso? For this, we conducted a qualitative research of documentary analysis using the interpretative analysis of the data produced based on Bogdan and Biklen (1994), Ludke and André (2013) and Sá-Silva; Almeida; Guindani (2009). The data production process was carried out on the set of official documents indicated for teacher training in the country and the 9 (nine) Pedagogical Projects of Courses (PPC) of Mathematics Degree from 3 (three) public institutions of Higher Education in the state from Mato Grosso. For the production of data we perform of the following procedures: interpretative analysis of the data produced, thus generating the enrichment and chaining of the knowledge generated through the instrument of reading records. In order to discuss the aspects of initial formation of the mathematics teacher, we rely mainly on Saviani (2005; 2009), Curi (2000), Leite (2016), Gatti (2014), Tardif (2002), Fiorentini and Oliveira (2013) , Moreira and Ferreira (2013), SBEM (2003) and Veiga (2004) to the relevance aspects of Pedagogical Projects of Courses. In addition, to address the issues surrounding the process of building knowledge on how to teach in the initial training of mathematics teachers, we report to: Mizukami (2004; 2008), Roldão (2007), Serrazinha (2014), Shulman (2014), Gauthier et al. (2013), Tardif (2002), Pimenta (2008) and among others. In response to the research problem, we highlight that we identified in several of the PPC the presence of referencing of knowledge on how to teach, even if not explicitly. Furthermore, the documentary analysis we carried out showed the deficiencies of some Mathematics Degree courses in the state of Mato Grosso. Accordingly, we demonstrate the relevance of this research for the development and improvement of the training of mathematics teachers and, consequently, for the development of quality education in the state.